Highlights of the 30th International Conference on Antiviral Research - Andrei, Graciela; Carter, Kara; Janeba, Zlatko; Sampath, Aruna; Schang, Luis M; Tarbet, E Bart; Vere Hodge, R Anthony; Bray, Mike; Esté, José A (Antiviral research, 2017)
The 30th International Conference on Antiviral Research (ICAR) was held in Atlanta, GA, USA from May 18 to 21, 2017. This report provides an account of award lectures, invited keynote addresses and oral presentations during the meeting. The 2017 Gertrude Elion Memorial Lecture Award by Michael Sofia highlighted one of the most important accomplishments in recent drug discovery in antiviral research, the identification of the hepatitis C virus direct-acting antiviral sofosbuvir and new alternatives to combat hepatitis B virus (HBV) infection. The Antonín Holý Lecture Award by David Chu on medicinal chemistry provided an overview of early developments of nucleoside analogs for the treatment of HIV and varicella zoster virus infection and how this knowledge serves to develop new drugs targeting HBV. Priscilla Yang gave the first ISAR Women in Science lecture. She reported on pharmacological validation of new antiviral targets for dengue, Zika and other flaviviruses. The William Prusoff Young Investigator Lecture Award by Maaike Everts described the Alabama Drug Discovery Alliance and the Antiviral Drug Discovery and Development Consortium, and how they are helping to accelerate the development of new antivirals. The 30th ICAR was a success in promoting new discoveries in antiviral drug development and research. The 31st ICAR will be held in Porto, Portugal, June 11-15, 2018.
Keywords: farmaceutická chemie; Zika Virus Infection; infekce virem zika; Antiviral Agents; hepatitida B; Drug Discovery; lidé; Chemistry, Pharmaceutical; Hepatitis B; dengue; objevování léků; antivirové látky; Dengue; Humans